Evaluation of benzo[a]pyrene-induced toxicity in the estuarine thornfish Therapon jarbua. (2022) - Sathikumaran, R.; Madhuvandhi, J.; Priya, KK; Sridevi, A.; Krishnamurthy, R.; Thilagam, H.
Abstract: Our previous study reported that chronic exposure to sublethal levels of estrogen induces DNA damage and endocrine dysfunction in sea bass. In this study, we extended our hypothesis to test changes in genotoxicity and biotransformation induced by Benzo[ a ]pyrene (BaP) that may regulate endocrine disorders in the estuarine fish. Therapon jarbua an euryhaline fish was exposed to BaP at two different ambient concentrations for 21 days. Biomarkers such as ethoxyresorufin-O-deethlylase (EROD) and DNA damages were assessed in the gill and liver, while neuroendocrine markers such as serotonin (5-HT) and acetyl cholinesterase (AChE) were studied in the brain. The findings showed that longer the exposure, higher the levels of biotransformation enzymes and DNA damage were produced. In both gill and the liver, BaP exposure generated dose-dependent EROD induction and DNA damages, with such a response being more linear in the case of liver than gill. BaP toxicity exacerbated the neurotoxicity by inhibiting acetylcholinesterase (AChE) activity and serotonin levels in the brain and this response was dose-dependent. Neuroendocrine system and biotransformation enzyme have a negative correlation. Results of the correlation and regression data suggest the reduction of endocrine marker might be attributed to the activation of biotransformation enzymes. These findings showed that BaP exposure can harm the gills and liver by inducing the biotransfomation enzyme and causing DNA damage, and so inhibiting neurotransmitters in the brain. These findings are predicted to give fresh insight on the research of the ecotoxicology effect of PAHs on estuarine fish. Graphical Abstract: ga1 Highlights: Biotransformation occurs in estuarine fish after a 21-day exposure to BaP. The method relies on the use of the commercial fish Terapon jarbua. In fish, BaP causes neurotransmitter modulation and DNA damage. The correlation analysis of the responses revealed that they were extremely significant. The first research to demonstrate that BaP-induced biotransformation affects neurotransmitters in fish.